Like Driving From "the Back Seat": Teaching English as a Second Language in Commodified Curricular Terrains. Issue 1 (2nd March 2017) - Plaisance, Michelle; Salas, Spencer; D'Amico, Mark M.
Abstract : Contemporary K–12 standards‐based educational reform has emerged as a central focus of scholarship in TESOL, with robust discussions (practical and theoretical) addressing the shift from ESL as a subject matter unto itself to teaching standards‐based content in English (and the standardized assessment of students' achievement across those content areas, including literacy and reading). However, relatively few studies have examined how veteran ESL professionals understand themselves and what their work accomplishes in instructional contexts where literacy and literacy test scores have emerged as the gold standard of adequate yearly progress. In this qualitative narrative, the researchers draw from a 7‐month study of an ESL teacher and her first‐grade colleagues' negotiation of a balanced literacy program. Analysis reveals that for this teacher the schoolwide adoption of "balanced literacy" created tensions between what she was expected to do and who she wanted to be or even was capable of being. It was only with great reluctance and even sadness that she realized that if she were to stay at her school and enact her professional functions with any degree of credibility, she would have to reconsider what teaching ESL could encompass. The authors conclude with implications for TESOL preservice and in‐service teacher education.